Antimicrobial Essential Oil Combinations to Combat Foot Odour - Orchard, Ané; Viljoen, Alvaro; van Vuuren, Sandy (Planta Medica, 2018)
Foot odour (bromodosis) is an embarrassing and perplexing condition mostly caused by bacteria of the Brevibacterium species. Essential oils are a credible option as an affordable treatment of odour and contribute towards antimicrobial efficacy. Therefore, this study sets out to investigate the antimicrobial activity of essential oil combinations against odour-causing bacteria. The broth microdilution method was used to investigate the antimicrobial activity of 119 essential oil combinations, and the fractional inhibitory index was calculated to determine the interactive profile. Combinations that resulted in synergy in 1 : 1 ratios were further evaluated in different concentrations, and isobolograms were plotted to determine the influence of the ratio on overall activity. Numerous combinations could be identified as having synergistic interactions against the Brevibacterium spp. and no antagonism was observed. The combination of Juniperus virginiana (juniper) and Styrax benzoin (benzoin) demonstrated synergy against all three Brevibacterium spp. tested and J. virginiana was the essential oil responsible for the majority of the synergistic interactions. The results reported here confirm the promising potential of the majority of these oils and selected combinations in treating and controlling bromodosis.
Keywords: aromatherapy; Brevibacterium spp.; bromodosis; malodour; interactions; essential oils; antimicrobial